Problem solving using artificial intelligence techniques - A.R. Greef; R. Reinecke (ORiON, 2003)
Real-world problems often do not lend themselves to an algorithmic solution. Humans, however, cope with these problems despite their fallible problem solving techniques. Instead of trying to construct algorithms to solve problems AI researchers have concentrated on using the more successful methods used by humans. This paper reviews the area of problem solving in the field of Artificial Intelligence. This includes problem representation for computation, "weak" methods of searching for a problems solution, knowledge representations that facilitate more efficient search strategies and planning - an advanced problem solving technique.